Learning System Management To Improve The Quality Of Learning Chemistry On Students Of State 8 Sma Negeri 8 Bekasi And Taman Students High School Of Bekasi - Hartanto, Hartanto; Suherman, Dadang; Warta, Waska; Cepi Barlian, Ujang (CV. Inara, 2022)
The quality of education is reflected by the competence of graduates which is influenced by the quality of the process and content of education. Achievement of graduate competencies that meet standards must be supported by educational content and processes that also meet standards. Currently students tend to solve a problem by imitating the problem solving demonstrated by the teacher when discussing questions. In addition, later students will find it difficult to apply concepts to solve non-routine problems and real problems related to the concepts that have been studied. This is what causes the low ability of students to solve problems. The research method used in this study is a descriptive method with a qualitative approach, this method is used to solve the problem under study where this research is aimed at extracting data and information related to the management of the learning system to improve the quality of student chemistry learning at SMA Negeri 8 and SMA Taman. Bekasi students. To obtain objective data in this study the authors used certain data collection methods and techniques. Data collection techniques were carried out by observation, interviews and documentation. Based on the results of the research, the Principal has carried out learning management, including: Mastering the outlines of the teaching program for each field of study and each class, Arranging school programs for one year, Arranging lesson schedules, Coordinating activities for formulating teaching unit models, Arranging activities assessment, Implementing the norms of grade promotion, Coordinating school guidance activities, Maintaining and developing school library books and learning tools. The Principal in learning management is responsible for the implementation of educational activities, school administration, coaching other educational staff, and the utilization and maintenance of facilities and infrastructure. In the implementation of relatively good learning, the teacher carries out learning activities including preliminary activities, core activities, and closing activities. The core activities consist of exploration, elaboration, and communication activities. The principal provides guidance, assistance, supervision and assessment on issues related to the technical implementation and development of teaching education in the form of improvement of teaching education programs and activities in order to create teaching and learning situations. The impact of the implementation of learning management on students and schools are: 1) school final exam results, 2) accreditation scores, 3) public trust and 4) on the academic and non-academic achievements of SMA Negeri 8 Bekasi students.